Preparation method of amorphous iron oxide microspheres for lithium battery

By employing a fully liquid process and a composite purification step, the problems of uncontrollable impurity content and low production efficiency in iron oxide production have been solved, enabling automated production of high-quality iron oxide and improving product qualification rate and battery performance.

CN120864565APending Publication Date: 2025-10-31GANSU YIFAN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511095143.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-06
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

In the existing production process of iron oxide for lithium batteries, the impurity content is uncontrollable, the product qualification rate is low, the production efficiency is low, and the labor intensity is high, making it difficult to achieve automated control.

Method used

Employing a fully liquid process, the process involves steps such as ferrous sulfate purification, ammonia preparation, seed crystal preparation, oxidation crystal growth, and deep phosphate purification. Using ferrous sulfate and liquid ammonia as raw materials, combined with an aminotrimethylenephosphonic acid/polyepoxysuccinic acid complex, iron oxide is purified to form a stable star-shaped colloid, selectively removing phosphate and achieving automated control.

Benefits of technology

It effectively controls the impurity content of products, improves the product qualification rate, realizes automated production, improves production efficiency, reduces labor intensity, and improves lithium-ion diffusion rate and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120864565A_ABST
    Figure CN120864565A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of amorphous iron oxide microspheres for a lithium battery, and relates to the technical field of battery materials, the preparation method comprises the following steps: using ferrous sulfate, liquid ammonia and liquid oxygen as raw materials to produce an iron oxide product which has high purity and high activity and is suitable for manufacturing a lithium iron phosphate battery, and simultaneously co-producing high-quality ammonium sulfate; the method comprises the following steps: (1) purifying ferrous sulfate, namely preparing ferrous sulfate heptahydrate and water into a solution, heating and stirring, adding ammonium sulfide and ammonia water to adjust the pH value of the solution, filtering, removing heavy metal ions, cooling and crystallizing to obtain ferrous sulfate crystals, and dissolving the crystals with pure water to obtain a pure ferrous sulfate solution; (2) preparing a seed crystal; (3) carrying out oxidation crystal growth and composite dephosphorization; and (4) filtering, washing, drying and crushing. According to the technical scheme, the problems that the iron oxide produced by the existing method for producing the iron oxide for the lithium battery has many impurities, the product percent of pass is uncontrollable, and the production efficiency is low are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery materials technology, and in particular to a method for preparing amorphous iron oxide microspheres for lithium batteries. Background Technology

[0002] In the production processes of lithium iron phosphate and lithium manganese iron phosphate batteries, the mainstream processes include the iron phosphate process, the iron nitrate process, and the iron oxide process. Each process has its own advantages and disadvantages, and they coexist. The iron oxide product produced by this invention is used in the production of lithium batteries using the iron oxide process, and can also be used in the production of lithium replenishing agents. The iron oxide process for lithium batteries has two main quality requirements for the raw material iron oxide: its reactivity and its impurity content. The reactivity of iron oxide is controlled by adjusting the shape, particle size, and uniformity of the primary iron oxide crystals, while the impurity content can only be controlled by adjusting the purity of the raw materials.

[0003] The existing iron oxide production process is a semi-liquid phase method, using iron scrap, nitric acid, and sulfuric acid as the main raw materials. The specific process is as follows: thin iron scrap and nitric acid are heated and pressurized in a reaction vessel to produce seed crystals. These seed crystals are then added to an oxidation reaction tank, along with iron scrap and ferrous sulfate. The tank is heated with steam and air is introduced for oxidation. The ferrous sulfate in the oxidation reaction tank is oxidized to produce iron oxide and sulfuric acid. The sulfuric acid then reacts with the iron scrap to produce ferrous sulfate again, forming a cyclical reaction. The iron scrap is continuously consumed and eventually converted into iron oxide.

[0004] The disadvantages of this process are several: First, the impurity content in the raw iron sheet is uncontrollable and its source is unstable, making it impossible to effectively remove impurities during production, resulting in excessive impurity content in the product and a low product qualification rate. Second, the iron sheet is an irregularly shaped block of varying sizes, requiring manual feeding during production, which is labor-intensive and difficult to automate. Third, after the reaction, a considerable amount of iron sheet residue remains in the oxidation tank, carrying a lot of iron oxide slurry, which must be thoroughly cleaned to avoid affecting the quality of the next batch of products. Cleaning these residues can only be done manually, which is time-consuming and labor-intensive, leading to low production efficiency. In particular, phosphate ions may be present in the raw materials, and phosphate ions combine with iron ions to form colloids that are difficult to remove, embedding in the crystal lattice and causing distortion, reducing the lithium ion diffusion rate, etc. Summary of the Invention

[0005] This application provides a method for preparing amorphous iron oxide microspheres for lithium batteries, which solves the problems of high impurity content, uncontrollable product qualification rate, and low production efficiency in the existing methods for producing iron oxide for lithium batteries.

[0006] This application provides a method for preparing amorphous iron oxide microspheres for lithium batteries, including: 1. Ferrous sulfate purification, the purification steps are as follows: Ferrous sulfate is dissolved or diluted with water to prepare an aqueous solution with a concentration of 300 g / L-650 g / L. The solution is heated to 60℃-90℃, and ammonium sulfide is added under stirring. The amount of ammonium sulfide added is 0.05%-0.5% of the amount of ferrous sulfate. Ammonia water is then added to adjust the pH of the solution to 3.8-4.5. The solution is then filtered through a membrane filter. The amount of suspended solids in the filtered solution (Y1) is less than 10 ppm. The filtrate (Y1) is passed through an ion exchanger to adsorb impurity ions, ensuring that the heavy metal ion content is <0.2 ppm. The flow rate of the filtrate (Y1) through the adsorption resin is 10 m / s. 3 -40m 3 Every hour, a solution (Y2) is obtained after exiting the ion exchanger; The solution (Y2) was placed in a crystallization vessel and cooled to 5℃-15℃. Ferrous sulfate crystals were precipitated, filtered to obtain crystals, and dissolved in pure water to prepare a ferrous sulfate solution (Y3) with a concentration of 300g / L-400g / L. 2. Preparation of ammonia water, the steps are as follows: Liquid ammonia and pure water are used to prepare ammonia water with a concentration of 10%-25% through an ammonia absorber; 3. Seed crystal preparation, the steps are as follows: (1) Primary seed crystal Ferrous sulfate solution (Y3) is diluted with pure water, stirred and neutralized with ammonia water, and then oxygen is introduced for oxidation. After oxidation, primary seed crystals are obtained. The process conditions for preparing primary seed crystals are as follows: Ferrous sulfate concentration: 10g / L-60g / L (preferably 30g / L-40g / L); pH value after neutralization: 8-10 (preferably 8.5-9.5); Oxygen flow rate: 0.1 m³ 3 -0.5m 3 per hour; Oxidation temperature: 10℃-35℃ (preferably 22℃-28℃); Oxidation time: 3-4 hours; (2) Target seed crystal, the steps are as follows: The primary seed crystals were heated to 80℃-95℃ and stirred. A seed conversion inducer was added. Under the action of the inducer, the primary seed crystal γ-FeOOH was rapidly converted into the target seed crystal α-Fe2O3 in 60min-90min. The particle size of the converted target seed crystals was approximately 0.08μm-0.1μm, and the shape was spherical. The inducer used for the conversion was ferric sulfate. 4. Oxidation crystal growth The target seed crystal is stirred and added to a ferrous sulfate solution (Y3). Steam is introduced for heating and oxygen is introduced. As the oxidation reaction proceeds, the generated iron oxide adheres to the surface of the seed crystal, and the seed crystal gradually grows. When the crystal particles grow to the required particle size, the reaction can be terminated and the material discharged. The oxidation crystal growth process conditions are as follows: Ferrous sulfate concentration: 10g / L-60g / L (preferably 30g / L-40g / L); Oxidation pH: 2.8-4.5 (preferably 3.5-4.0); Oxygen flow rate: 0.1 m³ 3 -0.5m 3 per hour; Oxidation temperature: 80℃-95℃ (preferably 85℃-90℃); Oxidation time: 40h-60h; 5. Deep purification of phosphate ions, the steps are as follows: After oxidation crystallization, the slurry is cooled to 40±2℃. 1.5-2.0 L of an aminotrimethylenephosphonic acid / polyepoxysuccinic acid complex solution (5 wt%) is added per cubic meter of slurry. The mixture is stirred at low speed (50-100 rpm) for 45 minutes to allow the complex to fully complex the free phosphate ions (PO4) in the slurry. 3- ); to obtain slurry (Y4); The preparation method of the aminotrimethylenephosphonic acid / polyepoxysuccinic acid composite is as follows: aminotrimethylenephosphonic acid (10 wt%) and polyepoxysuccinic acid (12 wt%) are mixed at a volume ratio of 1:1, and 0.1 vol% ethanol is added as a dispersant; the mixture is then subjected to isothermal sonication at 40℃ at 25 kHz and 0.5 W / cm². 3 Power density treatment for 30±2 min (forming star-shaped supramolecular structures with a particle size of 50±5 nm); static curing at 25℃ for 24 h (Zeta potential stabilized to -35 mV). 6. Filter and wash with water, the steps are as follows: The slurry (Y4) is filtered, and the filtrate is a pure ammonium sulfate solution. The filter cake is washed with pure water to remove the ammonium sulfate, complexes and phosphate ions carried in the filter cake. The wash water containing ammonium sulfate is filtered through a 200 Da filter membrane to remove PESA residue and free phosphate ions and then returned to step 1 to dissolve ferrous sulfate. 7. Drying and pulverizing, the steps are as follows: The washed filter cake is dried at 120℃ until the moisture content is less than 0.5%, and then pulverized to a fineness of less than 400 mesh to obtain iron oxide material for lithium iron phosphate batteries. A small amount of residual phosphate ions form nano-sized iron phosphate during pulverization. The trace amount of FePO4 (<50ppm) is compatible with the composition of the positive electrode material of lithium iron phosphate batteries and has no side effects. On the contrary, its stable lattice ensures voltage stability, improves rate performance, and improves battery cycle life and high-temperature storage capacity decay.

[0007] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages: The ammonium sulfate solution obtained in step 6 is evaporated using MVR or multi-effect evaporation. The concentrated evaporation solution is then crystallized, centrifuged, and dried to obtain a high-quality ammonium sulfate product. The condensate generated during evaporation is used to wash the iron oxide filter cake, and then used to dissolve ferrous sulfate heptahydrate. The utilization of water achieves a closed-loop cycle.

[0008] Using ferrous sulfate and liquid ammonia as raw materials, purification can be carried out at the raw material stage to remove all impurities that affect product quality, thereby effectively controlling the impurity content in the product and significantly improving the product qualification rate; moreover, the entire production process is carried out in liquid form, which facilitates automated control and results in high production efficiency.

[0009] In polyepoxysuccinic acid, the carboxyl group forms a stable star-shaped colloidal structure through steric hindrance effect, including the phosphate-aminotrimethylenephosphonic acid complex. The aminotrimethylenephosphonic acid forms a strong coordination bond based on phosphate through phosphonic acid, which has a much higher selectivity than other anions. After the complex binds to phosphate, the site changes from -35mV to -10 to -15mV and then agglomerates, making it easy to remove. Furthermore, the complex reduces the surface charge of iron oxide, thereby reducing the adsorption of sodium sulfate, reducing washing water consumption, decreasing the moisture content of the filter cake, and shortening the drying time. Attached Figure Description

[0010] Figure 1 This is a SEM image of the primary seed crystal obtained in Example 1 of the present invention; Figure 2 This is an electron microscope (TEM) image of the target seed crystal obtained in Example 1 of the present invention; Figure 3 This is an electron microscope (TEM) image of the iron oxide product obtained in Example 1 of the present invention. Detailed Implementation

[0011] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to limit the invention; the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0012] Example 1: A method for preparing amorphous iron oxide microspheres for lithium batteries, comprising the following steps: (1) Add 80 kg of pure water to a 200 L enamel reactor, stir, add 80 kg of ferrous sulfate heptahydrate (a byproduct of a titanium dioxide plant), heat to 60 °C, add 400 ml of freshly prepared 10% ammonium sulfide solution, stir for 20 minutes, then slowly add 28% analytical grade ammonia water to adjust the pH of the solution to 3.8, continue to maintain the temperature at 60 °C for 30 minutes, then pump into a small membrane filter with a filtration area of ​​1 square meter for heat preservation filtration, to obtain a clear, transparent, light green solution. Add the above solution to an ion exchange column containing 5 L of adsorption resin, control the flow rate of the solution through the ion exchange column at 1 L / min, keep the temperature throughout the ion exchange process, and ensure that the temperature of the solution after exchange is not less than 50 °C. Place the solution after ion exchange into a 200 L jacketed crystallizer, lower the solution temperature to 10 °C with chilled brine, filter after ferrous sulfate crystallizes out, and then dissolve the crystals in pure water to prepare a pure ferrous sulfate solution with a concentration of 300 g / L.

[0013] (2) Take 4L of pure ferrous sulfate solution and add it to a 100L seed tank. Dilute it with pure water to a concentration of 20g / L, stir, and slowly add 28% analytical grade ammonia water to adjust the pH of the slurry to 8.0. Introduce oxygen at a flow rate of 100ml / min (0.1m3 / h.m3) for 195 minutes to obtain primary seed crystals. The reaction temperature is maintained at 25℃ throughout the oxygenation process. Heat the primary seed crystals to 80℃, stir, add 50g of inducing agent, continue stirring and keep at 80℃. The conversion ends after 78 minutes to obtain the target seed crystals.

[0014] (3) Transfer the target seed crystals into a 150L oxidation tank, stir, and add 6L of the pure ferrous sulfate solution from step (1) at once. Analyze the ferrous sulfate concentration in the slurry in the oxidation tank to be 32g / L. Heat the seed crystals to 80℃ and start the automatic temperature control. Set the temperature control target value to 80℃, and then start the automatic pH control device. Adjust the amount of ammonia added according to the pH value detected by the pH electrode. Set the pH control target value to 3.0. The ammonia used is analytical grade ammonia. Introduce oxygen into the oxidation tank at a flow rate of 150ml / min. Continuously add the pure ferrous sulfate solution using a peristaltic pump. Take samples every 4 hours to analyze the concentration of ferrous sulfate in the slurry. Adjust the peristaltic pump to control the amount of ferrous sulfate added according to the analysis results, so that the ferrous sulfate concentration in the oxidation tank is controlled at 30-40g / L, with a minimum of 10g / L and a maximum of 60g / L. After 40 hours of reaction, samples are taken to test the crystal size, and the test is performed every 8 hours. When the crystal size is close to the final product requirement (compared with the standard sample), the addition of ferrous sulfate is stopped, and ammonia is added to continue the reaction until the concentration of ferrous sulfate in the slurry drops to 0. Then, the addition of oxygen is stopped, heating and temperature control are stopped, the pH control device is turned off, and the reaction is terminated.

[0015] After the oxidation crystallization is completed, the slurry is cooled to 40°C, and 1.5L of aminotrimethylenephosphonic acid / polyepoxysuccinic acid composite solution (concentration 5 wt%) is added per cubic meter of slurry; the mixture is stirred at low speed (100 rpm) for 45 min to obtain the composite slurry. (4) The composite slurry is filtered by a 20L Buchner filter. The filtrate is 200Da after filtration and is an ammonium sulfate solution, which is used for evaporation and crystallization to produce ammonium sulfate. The filter cake is washed with pure water until the conductivity of the effluent is close to that of pure water. The filter cake is then taken out and placed in an oven at a constant temperature of 120℃ to dry. It is then pulverized to a fineness of 400 mesh using a sample pulverizer.

[0016] Example 2: A method for preparing amorphous iron oxide microspheres for lithium batteries, comprising the following steps: (1) Add 70 kg of pure water to a 200 L enamel reactor, stir, add 90 kg of ferrous sulfate heptahydrate (a byproduct of a titanium dioxide plant), heat to 70 °C, add 500 ml of freshly prepared 10% ammonium sulfide solution, stir for 20 minutes, then slowly add 28% analytical grade ammonia water to adjust the pH of the solution to 4.0, continue to maintain the temperature at 70 °C for 30 minutes, then pump into a small membrane filter with a filtration area of ​​1 square meter for heat preservation filtration to obtain a clear, transparent, light green solution. Add the above solution to an ion exchange column containing 5 L of adsorption resin, control the flow rate of the solution through the ion exchange column at 1 L / min, keep the temperature throughout the ion exchange process, and ensure that the temperature of the solution after exchange is not less than 55 °C. Place the solution after ion exchange into a 200 L jacketed crystallizer, lower the solution temperature to 15 °C with chilled brine, filter after ferrous sulfate crystallization, and then dissolve the crystals in pure water to prepare a pure ferrous sulfate solution with a concentration of 350 g / L.

[0017] (2) Take 5L of pure ferrous sulfate solution and add it to a 100L seed tank. Dilute it with pure water to a concentration of 30g / L, stir, and slowly add 28% analytical grade ammonia water to adjust the pH of the slurry to 9.0. Introduce oxygen at a flow rate of 150ml / min (0.15m3 / h.m3) for 182 minutes to obtain primary seed crystals. The reaction temperature is maintained at 28℃ throughout the oxygenation process. Heat the primary seed crystals to 85℃, stir, add 50g of inducing agent, continue stirring and keep at 85℃. The conversion ends after 72 minutes to obtain the target seed crystals.

[0018] (3) Transfer the target seed crystals into a 150L oxidation tank, stir, and add 6L of the pure ferrous sulfate solution from step (1) at once. Analyze the ferrous sulfate concentration in the slurry in the oxidation tank to be 39g / L. Heat the seed crystals to 85℃ and start the automatic temperature control. Set the temperature control target value to 85℃, and then start the automatic pH control device. Adjust the amount of ammonia added according to the pH value detected by the pH electrode. Set the pH control target value to 3.5. The ammonia used is analytical grade ammonia. Introduce oxygen into the oxidation tank at a flow rate of 200ml / min. Continuously add the pure ferrous sulfate solution using a peristaltic pump. Take samples every 4 hours to analyze the concentration of ferrous sulfate in the slurry. Adjust the peristaltic pump to control the amount of ferrous sulfate added according to the analysis results, so that the ferrous sulfate concentration in the oxidation tank is controlled at 30-40g / L, with a minimum of 10g / L and a maximum of 60g / L. After 40 hours of reaction, samples are taken to test the crystal size, and the test is performed every 8 hours. When the crystal size is close to the final product requirement (compared with the standard sample), the addition of ferrous sulfate is stopped, and ammonia is added to continue the reaction until the concentration of ferrous sulfate in the slurry drops to 0. Then, the addition of oxygen is stopped, heating and temperature control are stopped, the pH control device is turned off, and the reaction is terminated.

[0019] After the oxidation crystallization is completed, the slurry is cooled to 40°C, and 2L of aminotrimethylenephosphonic acid / polyepoxysuccinic acid composite solution (concentration 5 wt%) is added per cubic meter of slurry; the mixture is stirred at low speed (500 rpm) for 45 min to obtain the composite slurry. (4) The composite slurry is filtered by a 20L Buchner filter. The filtrate is 200Da after filtration and is an ammonium sulfate solution, which is used for evaporation and crystallization to produce ammonium sulfate. The filter cake is washed with pure water until the conductivity of the effluent is close to that of pure water. The filter cake is then taken out and placed in an oven at a constant temperature of 120℃ to dry. It is then pulverized to a fineness of 400 mesh using a sample pulverizer.

[0020] Example 3: A method for preparing amorphous iron oxide microspheres for lithium batteries, comprising the following steps: (1) Add 60 kg of pure water to a 200 L enamel reactor, stir, add 100 kg of ferrous sulfate heptahydrate (a byproduct of a titanium dioxide plant), heat to 80 °C, add 500 ml of freshly prepared 10% ammonium sulfide solution, stir for 20 minutes, then slowly add 15% homemade ammonia solution (liquid ammonia dissolved in pure water), adjust the pH of the solution to 4.5, continue to maintain the temperature at 80 °C for 30 minutes, then pump into a small membrane filter with a filtration area of ​​1 square meter for heat preservation filtration, to obtain a clear, transparent, light green solution. Add the above solution to an ion exchange column containing 5 L of adsorption resin, control the flow rate of the solution through the ion exchange column to 1 L / min, keep the temperature constant throughout the ion exchange process, and ensure that the temperature of the solution after exchange is not less than 60 °C. After ion exchange, the solution is placed in a 200L jacketed crystallizer. The solution temperature is lowered to 20℃ using chilled brine. After ferrous sulfate crystals precipitate, they are filtered to obtain crystals. The crystals are then dissolved in pure water to prepare a pure ferrous sulfate solution with a concentration of 400g / L.

[0021] (2) Take 5L of pure ferrous sulfate solution and add it to a 100L seed tank. Dilute it with pure water to a concentration of 40g / L, stir, and slowly add 15% self-made ammonia water to adjust the pH of the slurry to 10.0. Introduce oxygen at a flow rate of 250ml / min (0.25m3 / h.m3) for 195 minutes to obtain primary seed crystals. The reaction temperature is maintained at 28℃ throughout the oxygenation process. Heat the primary seed crystals to 90℃, stir, add 50g of inducing agent, continue stirring and keep at 90℃. The conversion is completed after 68 minutes to obtain the target seed crystals.

[0022] (3) Transfer the target seed crystals into a 150L oxidation tank, stir, and add 6L of the pure ferrous sulfate solution from step (1) at once. Analyze the ferrous sulfate concentration in the slurry in the oxidation tank to be 48g / L. Heat the seed crystals to 90℃ and start the automatic temperature control. Set the temperature control target value to 90℃, and then start the automatic pH control device. Adjust the amount of ammonia added according to the pH value detected by the pH electrode. Set the pH control target value to 4.0. The ammonia used is homemade ammonia from liquid ammonia. Introduce oxygen into the oxidation tank at a flow rate of 250ml / min. Add the pure ferrous sulfate solution continuously using a peristaltic pump. Take samples every 4 hours to analyze the concentration of ferrous sulfate in the slurry. Adjust the peristaltic pump to control the amount of ferrous sulfate added according to the analysis results, so that the ferrous sulfate concentration in the oxidation tank is controlled at 30-40g / L, with a minimum of 10g / L and a maximum of 60g / L. After 40 hours of reaction, samples are taken to test the crystal size, and the test is performed every 8 hours. When the crystal size is close to the final product requirement (compared with the standard sample), the addition of ferrous sulfate is stopped, and ammonia is added to continue the reaction until the concentration of ferrous sulfate in the slurry drops to 0. Then, the addition of oxygen is stopped, heating and temperature control are stopped, the pH control device is turned off, and the reaction is terminated.

[0023] After the oxidation crystallization is completed, the slurry is cooled to 40°C, and 1.5L of aminotrimethylenephosphonic acid / polyepoxysuccinic acid composite solution (concentration 5 wt%) is added per cubic meter of slurry; the mixture is stirred at low speed (75 rpm) for 45 min to obtain the composite slurry. (4) The composite slurry is filtered by a 20L Buchner filter. The filtrate is 200Da after filtration and is an ammonium sulfate solution, which is used for evaporation and crystallization to produce ammonium sulfate. The filter cake is washed with pure water until the conductivity of the effluent is close to that of pure water. The filter cake is then taken out and placed in an oven at a constant temperature of 120℃ to dry. It is then pulverized to a fineness of 400 mesh using a sample pulverizer.

[0024] Comparative Example 1: The only difference from Example 1 is that the aminotrimethylenephosphonic acid / polyepoxysuccinic acid complex solution was not added.

[0025] Examples 1-3 were analyzed using a laser particle size analyzer and an integrated circuit-on-exchange spectrometer (ICP-OES). The results are shown in Tables 1 and 2.

[0026] Table 1. Detection results of laser particle size analyzer in the implementation case.

[0027] Table 2. Elemental content analysis results of the implementation case using ICP-OES

[0028] The removal of phosphate was detected; phosphate removal rate (ion chromatography (IC)) and total phosphorus content in iron oxide (ICP-OES) were measured; the results are shown in Table 3. Table 3 Results of phosphate removal experiments

[0029] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing amorphous iron oxide microspheres for lithium batteries, characterized in that, Includes the following steps: S1. Ferrous sulfate solution is prepared by adjusting the pH value to between 3.8 and 4.5 with ammonium sulfide and ammonia, then filtered through a membrane filter. The filtrate is then passed through an ion exchange column to remove heavy metal ions. After cooling and crystallization, ferrous sulfate crystals are obtained by filtration. The crystals are then dissolved in pure water to obtain a pure ferrous sulfate solution for purification. S2. Ferrous sulfate solution is neutralized to pH 8.0-10.0 with 10%-28% ammonia water, and then oxygen is introduced for oxidation. After oxidation, primary seed crystals are obtained, which are then heated to 80℃-95℃ and an inducing agent is added to convert them into target seed crystals. S3. Add pure ferrous sulfate solution to the target seed crystals, controlling the ferrous sulfate concentration to 10g / L-60g / L, heat to 80℃-95℃, add ammonia water to control the pH value within the range of 2.8-4.5, introduce oxygen, and after the oxidation reaction begins, simultaneously add ferrous sulfate solution and ammonia water to obtain iron oxide slurry; then cool the slurry to 40±2℃, and add 1.5-2.0 L of 5% concentration aminotrimethylenephosphonic acid / polyepoxysuccinic acid composite solution per cubic meter of slurry; Stir at low speed for 45 minutes to obtain a composite slurry; S4. The composite slurry is filtered, washed, dried, and pulverized to obtain high-purity iron oxide for lithium batteries.

2. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, The raw material, ferrous sulfate, is a byproduct of the sulfuric acid process titanium dioxide industry, namely ferrous sulfate heptahydrate or ferrous sulfate waste liquid. The pure water used refers to water with a conductivity of less than 10 μS / cm and free of organic compounds, or the condensate obtained by evaporation of the ammonium sulfate solution in this invention.

3. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, In step S1, the concentration of the ferrous sulfate heptahydrate solution prepared by dissolving it in water is 300 g / L-650 g / L, the heating temperature is 60℃-90℃, and the pH value of the solution after adding ammonium sulfide and ammonia is 3.8-4.

5.

4. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, In step S1, ammonium sulfide is used to remove impurity ions that form insoluble sulfides in the ferrous sulfate solution, and ammonia is used to adjust the pH value to remove impurity ions such as titanium, high-valence iron, and aluminum in the ferrous sulfate solution.

5. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 3, characterized in that, In step S1, the preferred method for filtering the ferrous sulfate solution is a membrane filter, and the amount of suspended solids in the filtered solution is less than 10 ppm, more preferably less than 5 ppm.

6. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, In step S2, the concentration of ferrous sulfate used to prepare the primary seed crystals is 10 g / L-60 g / L, preferably 30 g / L-40 g / L; the pH value is 8.0-10.0; the temperature is 10℃-35℃, preferably 22℃-28℃; the oxidant used is oxygen; the oxidation time is 3-4 hours; and the oxygen flow rate is 0.1 m³ / h per cubic meter of material. 3 -0.5m 3 .

7. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, In step S2, an inducing agent is added during the rapid transformation of the primary seed crystal into the target seed crystal. The amount of the inducing agent added is 0.1%-0.5%, the transformation temperature is 80℃-95℃, and the transformation time is 60min-90min.

8. The method for preparing amorphous iron oxide microspheres for lithium batteries according to claim 1, characterized in that, In step S3, the oxidation temperature for crystallization is 80℃-95℃, preferably 85℃-90℃. During oxidation, the pH value is controlled at 2.8-4.5, preferably 3.5-4.

0. The ferrous sulfate concentration is controlled at 10g / L-60g / L. Oxygen is used as the oxidant, and the oxidation time is 40h-60h. The oxygen flow rate is 0.1m³ / h per cubic meter of material. 3 -0.5m 3 .